PERAN BADAN PENASIHAT PEMBINAAN DAN PELESTARIAN PERKAWINAN (BP4) DAN MEDIATOR PENGADILAN AGAMA SURABAYA DALAM MENANGANI KONFLIK RUMAH TANGGA - Fitrotin Jamilah; Vierna Nurihza Salsabila (Al Hakam : The Indonesian Journal of Islamic Family Law and Gender Issues, 2021)
This paper discusses the role of the advisory body for the development and preservation of marriage and the mediator of the Surabaya religious court in dealing with domestic conflicts. Judging from the observations in Surabaya, many married couples are not able to recognize the type of household conflict they are facing. They tend to resolve conflicts by going through a divorce, without ascertaining the lightness or severity of the problem; can still be resolved by referring or ending. This makes the divorce rate in Surabaya increasing. What the public needs to know is that there is a body that has been recognized by the Ministry of Religion, namely BP4 which is found in every KUA, which is a facility for married couples who need guidance in their household, resolve conflicts, and become a united family. The position of BP4 is equivalent to that of a Mediator in the Religious Courts in the field of resolving conflicts in the household, but different strategies and ways of resolving them. In this regard, the purpose of this thesis is to determine the role and strategy of resolving BP4 Surabaya and PA Surabaya Mediator in dealing with conflicts. household. The type of method used is descriptive qualitative, meaning that it does not use percentage calculations. Using interview techniques and supported by related literacy as a support for the thesis that will be carried out by researchers.